Assessment of Physicochemical Properties of Orange Juice Concentrate Formulated with Pectin, Xanthan, and CMC Hydrocolloids - Mehrdad Mohammadi; Mina Mahdavi-Yekta; S. Fatemeh S. Reihani; Nasim Khorshidian; Mahdi Habibi; Amin Mousavi Khaneghah (International Journal of Food Science)
Orange concentrate (OC) is one of the main raw materials in the nonalcoholic beverage industry. Considering the difference in orange varieties, preserving its natural quality is essential to yield a product with favorable attributes and physical stability. Thus, the present study is aimed at assessing the effect of pectin, xanthan, and carboxymethyl cellulose (CMC) in a concentration range of 0–0.2% (w/v) along with mixing temperature on Brix, pH, acidity, density, turbidity, and viscosity of OC and at calculating the model equation for each attribute. The results showed that, except for CMC, the influence of concentration, type, and amount of hydrocolloid on pH changes was insignificant. Adding each hydrocolloid individually, in pairs, or threes reduced the density, and the measured density was lower at a mixing temperature of 4°C. Also, it was observed that mixing temperature was the only factor influencing turbidity, and the values were significantly lower at 80°C compared to 4°C. A significant interaction effect of xanthan concentration and mixing temperature on the Brix was observed. Adding hydrocolloids, except pectin, resulted in a significant (p<0.05) increase in viscosity, and xanthan had the greatest effect on the viscosity. A suitable model was designed using pectin and xanthan, pectin and CMC, and all three gums, resulting in a final OC product with high stability and improved physical and chemical attributes. The optimized values for Brix, pH, acidity, density, turbidity, and OC viscosity were achieved using 0.08% pectin, 0.19% xanthan, and 0.08% CMC at 80°C mixing temperature.